Characterization of Photoluminescent Polylactone-Based Nanoparticles for Their Applications in Cardiovascular Diseases - Kuriakose, Aneetta E.; Pandey, Nikhil; Shan, Dingying; Banerjee, Subhash; Yang, Jian; Nguyen, Kytai T. (Frontiers in Bioengineering and Biotechnology, 2019)
Cardiovascular diseases (CVD) affect a large number of the population across the globe and are the leading cause of death worldwide. Nanotechnology-based drug delivery has currently offered novel therapeutic options to treat these diseases, yet combination of both diagnostic and therapeutic abilities is further needed to understand factors and/or mechanisms that affect the treatment in order to design better therapies to challenge CVD. Biodegradable photoluminescent polylactones (BPLPLs) enable to bridge this gap as these materials exhibit a stable, long-term intrinsic fluorescence as well as offers excellent cytocompatibility and biodegradability properties. Herein, we formulated three different BPLPL based nanoparticles (NPs), including BPLP-co-poly (L-lactic acid) (BPLPL-PLLA), BPLP-co-poly (lactic-co-glycolic acid) copolymers with lactic acid and glycolic acid ratios of 75:25 (BPLPL-PLGA75:25) and 50:50 (BPLPL-PLGA50:50), and extensively evaluated their suitability as theranostic nanocarriers for CVD applications. All BPLPL based NPs were <160nm in size with photoluminescence characteristics along with tunable release kinetics of encapsulated therapeutic agents and biodegradation depending on polylactones copolymerized with BPLP materials. Compared to BPLPL-PLLA NPs, BPLPL-PLGA NPs demonstrated excellent stability in various formulations including deionized water, serum, saline and simulated body fluid over 2 days. In vitro cell studies with human umbilical vein derived endothelial cells showed dose-dependent accumulation of BPLPL-based NPs, and BPLPL-PLGA NPs presented superior compatibility with endothelial cells in terms of viability with minimal effects on cellular functions such as nitric oxide production. Furthermore, all BPLPL NPs displayed hemocompatibility with no effect on whole blood kinetic profiles, were non-hemolytic, and consisted of comparable platelet responses such as platelet adhesion and activation to those of PLGA, an FDA approved material. Overall, our results demonstrated that BPLPL-PLGA based NPs have better physical and biological properties than BPLPL-PLLA; hence they have potential to be utilized as functional nanocarriers for therapy and diagnosis of CVD.